Unfinished nursing care in four central European countries - Zeleníková, Renáta; Gurkova, Elena; Friganovic, Adriano; Uchmanowicz, Izabella; Jarosova, Darja; Žiaková, Katarína; Plevová, Ilona; Papastavrou, Evridiki (My University, 2020)
Aim: The main aim of the research was to describe and compare unfinished nursing care in selected European countries. Background: The high prevalence of unfinished nursing care reported in recently published studies, as well as its connection to negative effects on nurse and patient outcomes, has made unfinished care an important phenomenon and a quality indicator for nursing activities. Methods: A cross-sectional descriptive study was undertaken. Unfinished nursing care was measured using the Perceived Implicit Rationing of Nursing Care questionnaire (PIRNCA). The sample included 1,353 nurses from four European countries (Croatia, the Czech Republic, Poland and Slovakia). Results: The percentage of nurses leaving one or more nursing activities unfinished ranged from 95.2% (Slovakia) to 97.8% (Czech Republic). Mean item scores on the 31 items of the PIRNCA in the total sample ranged from 1.13 to 1.92. Unfinished care was significantly associated with the type of hospital and quality of care. Conclusion: The research results confirmed the prevalence of unfinished nursing care in the countries surveyed. Implications for Nursing Management: The results are a useful tool for enabling nurse managers to look deeper into nurse staffing and other organizational issues that may influence patient safety and quality of care.
Keywords: Hospital nurses; PIRNCA; Survey; Unfinished nursing care